The Algorithmic Leviathan: Artificial Intelligence, the Reshaping of Political Power, and the Existential Threat to Human Agency - Ashikur Rahman (Darul Yasin Al Sys, 2026)
Artificial intelligence (AI) has evolved from a technological innovation into a strategic instrument of political power that is central to governance and international influence. In the contemporary world, AI systems mediate the production, distribution, and perception of information, thereby reshaping relations between citizens, governments, and states. This paper examines the complex role of AI in global politics—ranging from election manipulation and propaganda to cyber warfare, digital surveillance, and transnational crime—showing how AI-driven technologies now permeate nearly all spheres of human interaction and operate at the intersection of political communication, control, and persuasion through algorithmic and data-driven processes. Combining theoretical analysis with empirical case evidence, the study employs frameworks such as technopolitics, algorithmic governance, and political communication theory to conceptualize AI simultaneously as a politically active actor and as a technological tool of power. Drawing on case studies, it analyzes how states and political entities deploy AI to gain strategic advantage: in Russia, AI has been associated with disinformation operations, fabricated media content, and coordinated social media manipulation aimed at influencing foreign elections and undermining democratic institutions; in the United States, AI-driven data analytics and sentiment modeling have transformed electoral campaigning by enabling hyper-personalized voter targeting, while raising profound concerns about privacy and political manipulation; and in Bangladesh, reports of the Awami League’s use of AI-assisted bot networks and synthetic digital content illustrate the growing role of AI in shaping domestic political discourse. Collectively, these dynamics demonstrate that AI now functions as a core vector of political power in an interconnected world, intensifying long-standing debates over sovereignty, legitimacy, and democratic accountability.